Cabazitaxel multiple rechallenges in metastatic castration‐resistant prostate cancer. (12th August 2021) - Pobel, Cedric; Auclin, Edouard; Teyssonneau, Diego; Laguerre, Brigitte; Cancel, Mathilde; Boughalem, Elouen; Noel, Johanna; Brachet, Pierre Emmanuel; Maillet, Denis; Barthelemy, Philippe; Helissey, Carole; Thibault, Constance; et al.
Abstract: Introduction: Cabazitaxel multiple rechallenges may be a treatment option in heavily pretreated patients with metastatic castration‐resistant prostate cancer (mCRPC) who had a good initial response to cabazitaxel and who are still fit to receive it. Our objective was to assess the efficacy and toxicity of multiple rechallenges. Patients and methods: We retrospectively identified 22 mCRPC patients previously treated with docetaxel and/or androgen receptor‐targeted agents who received multiple cabazitaxel rechallenges in 9 French centers. Cabazitaxel was initiated at a dose of 25 mg/m 2 q3week. A reduced dose (20 mg/m 2 q3w) or an alternative schedule (mainly 16 mg/m 2 q2w) was increasingly used for subsequent rechallenges. Progression‐free survival, prostate‐specific antigen (PSA) response, best clinical response, and grade ≥3 toxicities were collected. Overall survival was calculated from various time points. Results: Twenty‐two patients with an initial response to cabazitaxel were rechallenged at least twice. The median number of cabazitaxel cycles was 7 at first cabazitaxel treatment, 6 at first rechallenge, and 5 at subsequent rechallenges. Median progression‐free survival at first rechallenge was 9.6 months and 5.6 months at second rechallenge. Median overall survival was 50.9 months from the first cabazitaxel dose, 114.9 months from first life‐extending therapy initiation in mCRPC, and 105 months from mCRPC diagnosis. There was no cumulative grade ≥3 neuropathy or nail disorder and one case of febrile neutropenia. Conclusion: Cabazitaxel multiple rechallenges may be a treatment option without cumulative toxicity in heavily pretreated patients having a good response to first cabazitaxel use and still fit to receive it. Novelty & Impact Statements: Patients with metastatic castration‐resistant prostate cancer can be treated with Cabazitaxel after docetaxel and androgen receptor‐targeted agent. This chemotherapy can be used multiple times with efficacy and manageable toxicity. Abstract : We assessed the efficacy and toxicity of multiple rechallenges with cabazitaxel for 22 patients with metastatic castration‐resistant prostate cancer (mCRPC). Median overall survival was 50.9 months from the first cabazitaxel dose, 114.9 months from first life‐extending therapy initiation in mCRPC, and 105 months from mCRPC diagnosis. Cabazitaxel rechallenge may be an effective option in heavily pretreated mCRPC patients with a good initial response to cabazitaxel and still fit to receive it, without cumulative grade ≥3 toxicity.